Ecosystem resilience to late-Holocene climate change in the Upper Zambezi Valley - Burrough, S; Willis, K (SAGE Publications, 2015)
Peat deposits from wetlands in the Upper Zambezi Valley provide an important long-term window on ecosystem dynamics in the Kalahari basin during the late Holocene. We use fossil pollen and macro-charcoal extracted from peat cores contained in three wetland sites to examine the response of vegetation to regional climate change. We find that during the last 6 ka, internal ecosystem dynamics are more important than climate, as observed by independent records, in determining vegetation assemblage change. Fire was found to be a persistent and important component of this savanna landscape for the duration of the ecological record, but biomass burning has increased markedly over the last 1000 years. The vegetation of the Upper Zambezi Valley appears to have a larger grassland component in the last few hundred years suggesting a more open landscape today than at any other time in the last 6000 years.